2019
DOI: 10.3390/min9110697
|View full text |Cite
|
Sign up to set email alerts
|

Selective Parameters and Bioleaching Kinetics for Leaching Vanadium from Red Mud Using Aspergillus niger and Penicillium tricolor

Abstract: In the present study, using Aspergillus niger and Penicillium tricolor, the influence of the selected parameters, including sucrose concentration, inoculation size of spores, pulp density, and pre-culture time, on the bioleaching efficiency (biomass, organic acids production, and vanadium extraction, respectively) of red mud were studied. The bioleaching kinetics under optimal conditions were also explored. Sucrose concentration showed a positive linear effect on bioleaching efficiency below 143.44 and 141.82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…of these studies reported that biogenic organic acids (culture supernatants) outperformed chemical leaching of comparable assays with pure organic acids (Reed et al, 2016;Qu et al, 2019).…”
Section: Abiotic Organic Acid Leaching Of the Magnetite Concentratementioning
confidence: 99%
See 1 more Smart Citation
“…of these studies reported that biogenic organic acids (culture supernatants) outperformed chemical leaching of comparable assays with pure organic acids (Reed et al, 2016;Qu et al, 2019).…”
Section: Abiotic Organic Acid Leaching Of the Magnetite Concentratementioning
confidence: 99%
“…Bioleaching strategies have also been tested for vanadium recovery including oxidative and organic acid leaching from spent catalysts by Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans, and Aspergillus niger (Muddanna and Baral, 2019;Mikoda et al, 2020;Pradhan et al, 2021); shale by At. ferrooxidans (He et al, 2019); red mud with the fungi A. niger and Penicillium tricolor (Qu et al, 2019); and steel slag by a mixed consortium of acidophilic bacteria dominated by At. ferrooxidans and At.…”
Section: Introductionmentioning
confidence: 99%
“…The main raw materials for vanadium extraction are titanomagnetite ores [11][12][13][14][15]. Vanadium can be extracted from coal, spent catalysts, ash from thermal power plants, and other sources [16][17][18][19][20][21]. Russia is one of the world s leading producer of vanadium.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the bioleaching of different ores and industrial wastes [24][25][26]; only a few, however, involve the bioleaching of BR, especially for REE extraction [18,22,27]. Fungal strains such as Penicillium tricolor [18,27] and Aspergillus niger [27][28][29] and microalgae [30] such as Desmodesmus quadricauda, Chlamydomonas reinhardtii, and Parachlorella kessleri have been investigated. However, the main disadvantages of the use of fungi and microalgae compared to bacteria are the generation of a large amount of biomass and spores, which increase the cost of the process and cause secondary pollution, and the separation of BR particles from fungal biomass after bioleaching is challenging [22].…”
Section: Introductionmentioning
confidence: 99%